De la police au tribunal : formulation et cheminement des plaintes portées devant la Cour du Québec, Chambre criminelle et pénale - Cousineau, Marie-Marthe; Cucumel, Guy (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1991)
To date, no one really knows exactly how cases go through the maze of legal proceedings after being filed. Based on a sampling ofl 795 requests to undertake legal proceedings presented by the Montreal Urban Community Police Service to "la Cour du Québec, chambre criminelle et pénale" (Quebec Criminal Court) and dealt with by this tribunal in 1989, the authors take a close look at how the intervention of the police (usual access to the judiciary system) and the intervention of the tribunal (decision making element of prime importance) are linked. Greater importance is given to three particular aspects of this matter. First, the authors consider how the police and the tribunal formulate the accusation. This allows them to throw a new light on the problem of over charging. Secondly, the authors reflect on the equally questionable issue of temporary custody at both the police and the tribunal levels. Finally, the authors conclude by examining the processing of cases at the tribunal level.